The Effect Of Service Quality and Promotion On Customer Loyalty With Customer Satisfaction as a Moderating Variable at PT. Global Trans Nusa - Tengku Monica Tan; Sofiyan Sofiyan; Hendry Hendry; Alex Tribuana Sutanto (CV. Aksara Global Akademia, 2024)
The purpose of this study was to determine the effect of service quality and promotion on customer loyalty with customer satisfaction as a moderating variable at PT Global Trans Nusa. The method used in this research is quantitative descriptive method which is carried out through data collection using questionnaires and statistical testing data analysis. The sample taken in this study were all customers who had used the services of PT Global Trans Nusa, totaling 85 people. The data analysis used is MRA analysis using the IBM SPSS Statistics version 26 application. The results showed that Service Quality has an effect on Customer Loyalty at PT Global Trans Nusa. Promotion has an effect on Customer Loyalty at PT Global Trans Nusa. Service Quality and Promotion affect Customer Loyalty at PT Global Trans Nusa. Customer Satisfaction cannot moderate the effect of Service Quality on Customer Loyalty at PT. Global Trans Nusa. Customer Satisfaction cannot moderate the effect of Promotion on Customer Loyalty at PT. Global Trans Nusa. Customer Satisfaction cannot moderate the effect of Service Quality and Promotion on Customer Loyalty at PT. Global Trans Nusa.